If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -26 = -26 Reorder the terms: -26 + 4x = -26 Add '26' to each side of the equation. -26 + 26 + 4x = -26 + 26 Combine like terms: -26 + 26 = 0 0 + 4x = -26 + 26 4x = -26 + 26 Combine like terms: -26 + 26 = 0 4x = 0 Solving 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '4'. x = 0 Simplifying x = 0
| 2(5x-1)=-5x-17 | | -3(y+5)+5y=2(y-6) | | x+10=5x-2 | | 6k-2+4=24 | | 4(2x-4)=5x-28 | | x-43=4(2x-2) | | 0=-38t | | 7y+y=46 | | 4x+78=-26 | | 7x+10=6x+21 | | 5(2x+3)+10=35 | | 3a+9+4a= | | 4[(12+5)-256]= | | h^2+8h+12=0 | | 2(5x+3)-9=3x+18 | | 14x-3=6x+45 | | -12x-17=-86 | | 6k+6-2=24 | | x+z+y=12 | | 2(2x+5)=18 | | 9x+5=6x+29 | | 9x+11=5x+59 | | 5x-1=3(4x-5) | | 6g+3(-8+4g)=1-g | | 46+2x-x=27 | | -4(v+4)=3(v+4)+7 | | 2x^2+35x-123=0 | | x-(-7)=-21 | | x=3x-12 | | 5(4x+3)=35 | | 3.4t+0.08=4 | | m+10=-2 |